A Binomial Software Reliability Model Based on Coverage of Structural Testing Criteria - Crespo, Adalberto Nobiato; Jino, Mario; Pasquini, Alberto; Maldonado, José Carlos (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2000: Anais do XIV Simpósio Brasileiro de Engenharia de Software, 2000)
A new approach to software reliability modeling is discussed where variables indirectly related with software reliability are used to provide additional information for the modeling process. Previous studies, empirical evidences, and results from experiments indicate that there is a strong relationship between software reliability and coverage of program elements required to be exercised by structural testing criteria. In this vein, a Binomial software reliability Model Based on Coverage - BMBC - is proposed and discussed. The BMBC, the first software reliability model based on coverage, was assessed with test data from a real application, making use of the following structural testing criteria: all-nodes, all-edges, and potential-uses — a data-flow based family of criteria. Results from the experiments show a clear superiority of the BMBC over the traditional models and point to a very promising research direction in software reliability.